(untitled) (Asian Journal of Social Science Studies, 2025)
This study aims to search out the contribution of the participation of children in school places, especially in the classroom in front of teachers in life. It is a result of the documentary technique The promotion of the children’s right to participation in the school milieu or classroom is a key to participative leadership but can also lead to laissez-faire leadership even though it opens the door to visionary leadership. These children who rejoice in their right to participation practice coaching-based leadership, affiliative leadership, and the democratic. There is also a large place for participative leadership and directive leadership. In the future, society will be characterized by transformational leadership and transactional leadership.